Química e atividade biológica de Microlicia crenulata (DC.) Mart: atividade antioxidante e antimicrobiana para a conservação de alimentos - Maria do Carmo Pereira (2013)
Microlicia crenulata (DC.) Mart (Melastomataceae) has a very restricted occurrence, being considered endemic to the state of Minas Gerais, Brazil. To date, the species has been chemically only for taxonomic purposes. This work sought to obtain useful knowledge oils for the preservation of food. The chemical compositions of essential oils extracted by hydrodistillation and of volatile substances extracted by HS-SPME from aerial parts of the M. crenulata were evaluated. The in vitro antioxidant, antibacterial, antifungal, antiprotozoal and cytotoxic activities of M. crenulata were also studied. To evaluate the antioxidant activity, assays were performed with DPPH and ABTS. The antibacterial activity was estimated using the disk diffusion and microdilution techniques against Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa and Escherichia coli. The antifungal activity was evaluated in vitro (minimum inhibitory concentration) against the fungi Aspergillus niger, Aspergillus flavus, Saccharomyces cerevisiae, Candida parapsilosis, Candida tropicalis, Candida krusei, Candida dubliniensis, Candida albicans, Candida glabrata, Cryptococcus neoformans and Cryptococcus gattii. The antiprotozoal activity was studied against the chloroquine-resistant W2 clone of Plasmodium falciparum by the pLDH method. The in vitro cytotoxic activity was investigated against the HepG2 A16 cell line. The essential oil of M. crenulata consisted of a complex mixture, including mainly terpene compounds. There was a slight variation in the yield and chemical composition of the essential oil according to the phenological stages. The profiles of volatile compounds were different when the hydrodistillation and HS-SPME techniques were used. Acacetin was isolated from the dichloromethane fraction, this being the first report of the occurrence of this flavone in the Microlicia genus. Considerable antioxidant activity in vitro in assays with DPPH and ABTS was observed for M. crenulata. The highest antioxidant activities were observed for more polar fractions, and the best results were obtained for the ethanol fraction FE. The essential oil showed moderate inhibitory activity against P. aeruginosa, S. cerevisiae and A. flavus and weak activity against A. niger. It was not able to inhibit the growth of B. cereus, E. coli or S. aureus, and was not active against species of Candida and Cryptococcus at the highest concentration tested (250 g/mL). Moderate activities against strains of P. aeruginosa were observed for fractions extracted by Soxhlet, the methanol fraction and aqueous fraction. The ethyl acetate fraction presented weak activity against P. aeruginosa. For B. cereus, the results showed that the hexane and dichlorometane fractions were moderately active against the said bacteria. None of the tested fractions showed activity against E. coli and S. aureus. Hexane, methanol and aqueous fractions showed good activity against S. cerevisiae. The crude ethanol extract obtained by percolation and its fractions showed good inhibitory activity against yeasts. The best results were obtained for the inhibition of C. glabrata, C. dubliniensis and C. gattii, and the components responsible for the antifungal activity may be polyphenols, especially hydrolysable tannins. Regarding the in vitro antiplasmodial activity, five samples were active, one was moderately active, two were slightly active and six were inactive. The fractions showed in vitro antiplasmodial activity and good selectivity for the parasite in relation to HepG2 cells. Regarding the activities reported in this study there is the need to continue with the isolation of the active principles to ascertain whether a single compound is responsible for the activities or interaction with other compounds occurs.